Lip symmetry following rotation advancement cleft lip repair in 5-year-old children treated by Ralph Millard and Ron Pigott. (September 2022) - Maggiulli, F.; Hinton, C.; Simpson, L.; Gujral, S.; Hardwicke, J.; Slator, R.; Pigott, R.W.; Su, T.L.; Richard, B.
Abstract: Objective: To compare the symmetry of the lip following Rotation-Advancement cleft lip repair by Millard and Pigott and to investigate the effect on the symmetry of cleft side and gender by using different surgical protocols. Symmetry following cleft surgery was compared to that of non-cleft children. Design: Retrospective study of photographs of children aged 5 years. Setting: Three decades of post-operative photographs of children treated by Millard and Pigott. Patients: Eighty-nine children treated by Millard, 87 by Pigott and 91 non-cleft children. Interventions: Photographs were assessed using the Symnose Computer program, a rapid semi-objective quantitative assessment of lip symmetry. Main Outcome Measure(s): Asymmetry score for each surgeon, and non-cleft children. Results: There was no significant difference in the median lip % mismatch score of Millard, 36.65% and Pigott, 38.52%. Right-sided clefts showed better symmetry than left-sided clefts for Millard (p<.001). This was reversed for Pigott (P=.0121). There was a difference (P<.001) between the symmetry of the two cleft cohorts and the non-cleft children (asymmetry 19.9%), and between Millard's outcomes following different lip surgical protocols (P < .0001), but no difference between Pigott's outcomes using different palate surgical protocols (P = 0.59). Conclusions: Cleft lip repair by Millard and Pigott resulted in similar lip asymmetry (37% and 39% symmetry mismatch, respectively). Lip surgical protocol and cleft side may affect lip asymmetry. Palate surgery did not affect lip asymmetry. Following cleft surgery, children were more asymmetric than non-cleft children.